(untitled) (Journal of the College of Basic Education, 2026)
This research aims to assess the level of mathematical International in students in the Mathematics Department at the College of Basic Education. The researcher employed a descriptive analytical approach, as it aligns with the nature of the study. The research population comprised students from the Mathematics Department at Al-Mustansiriya University, while the sample was selected using a stratified random sampling method numbering (419). The sample included 66 students from the second year, 47 from the third year, and 78 from the fourth year. To achieve the research objectives, a specialized scale consisting of 26 items was developed, categorized into four primary dimensions of mathematical International. After administering the instrument to the sample, the study yielded the following findings: 1- Students in the Mathematics Department at the College of Basic Education demonstrate a proficient level of mathematical International. 2- Fourth-year students exhibit a level of mathematical International that significantly outperforms their peers in the second and third years. Based on these outcomes, the researcher proposed a set of pedagogical recommendations and suggestions for future studies.